Calcium Silicate-Based Biocompatible Light-Curable Dental Material for Dental Pulpal Complex - Sung-Min Park; Woo-Rim Rhee; Kyu-Min Park; Yu-Jin Kim; Junyong Ahn; Jonathan C. Knowles; Jongbin Kim; Jisun Shin; Tae-Su Jang; Soo-Kyung Jun; Hae-Hyoung Lee; Jung-Hwan Lee (Nanomaterials, 2021)
Dental caries causes tooth defects and clinical treatment is essential. To prevent further damage and protect healthy teeth, appropriate dental material is a need. However, the biocompatibility of dental material is needed to secure the oral environment. For this purpose, biocompatible materials were investigated for incorporated with dental capping material. Among them, nanomaterials are applied to dental materials to enhance their chemical, mechanical, and biological properties. This research aimed to study the physicochemical and mechanical properties and biocompatibility of a recently introduced light-curable mineral trioxide aggregate (MTA)-like material without bisphenol A-glycidyl methacrylate (Bis-GMA). To overcome the compromised mechanical properties in the absence of Bis-GMA, silica nanoparticles were synthesized and blended with a dental polymer for the formation of a nano-network. This material was compared with a conventional light-curable MTA-like material that contains Bis-GMA. Investigation of the physiochemical properties followed ISO 4049. Hydroxyl and calcium ion release from the materials was measured over 21 days. The Vickers hardness test and three-point flexural strength test were used to assess the mechanical properties. Specimens were immersed in solutions that mimicked human body plasma for seven days, and surface characteristics were analyzed. Biological properties were assessed by cytotoxicity and biomineralization tests. There was no significant difference between the tested materials with respect to overall physicochemical properties and released calcium ions. The newly produced material released more calcium ions on the third day, but 14 days later, the other material containing Bis-GMA released higher levels of calcium ions. The microhardness was reduced in a low pH environment, and differences between the specimens were observed. The flexural strength of the newly developed material was significantly higher, and different surface morphologies were detected. The recently produced extract showed higher cell viability at an extract concentration of 100%, while mineralization was clear at the conventional concentration of 25%. No significant changes in the physical properties between Bis-GMA incorporate material and nanoparticle incorporate materials.